RASIO KEUANGAN DAN PREDIKSI PERUBAHAN LABA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Syamsudin, Syamsudin; Primayuta, Ceky (Benefit: Jurnal Manajemen dan Bisnis, 2009)
The purpose of this study is to obtain empirical evidence of the influence of ratioanalysis to forecast changes in earnings. In this case the researchers used the data in the formof financial statements of listed manufacturing companies in Indonesia Stock Exchange (BEI).Researchers used sample of 32 manufacturing firms selected at random purposive sampling,the manufacturing companies listed on the Stock Exchange during 2007-2008 period. Thedata used are the financial statements audited financial statements as of December 31 in orderto avoid the presence of a partial financial statement data. Analysis tool used is multiple regressionanalysis, t test, F test, and coefficients of determination were tested with the classical assumption test. Based on the results of dataanalysis can be concluded that the variables CR andthe TATO has a significant influence on changes in earnings. As for the DER and NPM variables no significant effect on change in earnings.